Lysistrata - Ludovici, Anthony M. (Anthony Mario), 1882-1971; Haire, Norman, 1892-1952 (Salt Lake City, UT : Project Gutenberg, 2023)
"Lysistrata: or, Woman's Future and Future Woman" by Anthony M. Ludovici is a philosophical treatise that was likely written in the early 20th century. The work explores themes of femininity, societal values, and the roles of women in a modern context, directly engaging with the implications of these roles on their physical and moral well-being. It reflects on how women have adapted$1 (Bor have failed to adapt$1 (Bto the changing conditions of their lives and the resulting impact on their happiness and fulfillment. The opening of "Lysistrata" presents a foreword by Dr. Norman Haire, who praises Ludovici's stimulating insights while presenting a critical view of contemporary society's values regarding health and well-being. Dr. Haire's reflections suggest that the medical profession is failing to prioritize health over profit, particularly regarding women's health and societal roles. The introduction outlines the consistent neglect of women's physical needs and the deterioration of traditional values, hinting at a growing disillusionment with contemporary societal norms. Ludovici$1 (Bs treatise sets the stage for a deeper exploration into the present condition of women, framing their emotional and physical struggles within the context of a society distancing itself from natural, bodily realities. (This is an automatically generated summary.)s
Release date is 2023-01-07
Tim Lindell, Barry Abrahamsen, and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Women; Women -- Social and moral questions